Vocabulary Mastery and Short-Story Writing Ability: A Correlational Study at MTs Jâ-alHaq Bengkulu - Karlena, Elza Piro; Ansyah, Edi; Randi, Randi (Yayasan Darussalam Bengkulu, 2023)
This study aimed to determine the association between Indonesian vocabulary mastery and short-story writing ability among ninth-grade students at MTs Jâ-alHaq, Bengkulu City. Employing a correlational quantitative design, the research drew on a population of 362 students, from which 56 were sampled. Vocabulary mastery was measured using a multiple-choice test, whereas short-story writing ability was assessed with an analytic rubric. Data were analyzed via simple linear regression (SPSS 16). The normality assumption was satisfied (X: p = .449; Y: p = .059). However, the deviation-from-linearity test yielded p = .033, indicating a departure from strict linearity and warranting caution in interpreting the regression model. The regression coefficient was significant (b = 0.266, SE = 0.079, t(54) = 3.354, p = .001), indicating a positive association between vocabulary mastery and writing performance. In conclusion, vocabulary mastery is a positive predictor of short-story writing ability; nonetheless, the detected nonlinearity suggests follow-up modeling such as transformation or curvilinear specifications to produce more accurate estimates.